Secessionism and minority protection in an uncertain world - Vincent Anesi (The University of Nottingham, Centre for Decision Research and Experimental Economics (CeDEx), 2010)
With the changing economic circumstances confronting their countries, regionally concentrated minorities have been facing a strategic problem, important aspects of which can be stylized as a situation in which a minority leader is uncertain about the costs of secession for her community. This paper shows that this uncertainty is a central cause of secession, using a model which incorporates both policies to appease secessionist aspirations and informational asymmetries. In a situation of asymmetric information, in which the policy-maker is better informed about the consequences of separation than the minority leader, signaling incentives make secession the unique equilibrium outcome, whether mutually advantageous compromises exist or not. We also show that the ruling majority may seek to maintain political unity by pre-committing to minority protection rules which prevent bluffing by the informed policy-maker. Additionally, the model generates comparative statics results on the question of which states are most likely to adopt constitutional rules protecting the minorities living within their borders.
Keywords: D74; D82; H77; 330; constitutional commitment; secession; signaling; regional redistribution; Minderheit; Regionale Konzentration; Minderheitenpolitik; Asymmetrische Information; Signalling; Separatismus; Theorie